What is the value of 2 ( sin 6 θ + cos 6 θ ) − 3 ( sin 4 θ + cos 4 θ ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you for the nice solution.
Hee hee. Since it can be assumed the value is constant for all θ , we can substitute θ = 0 , noting sin n ( 0 ) = 0 , ∀ n and cos n ( 0 ) = 1 , ∀ n . So 2 ( sin 6 θ + cos 6 θ ) − 3 ( sin 4 θ + cos 4 θ ) = 2 ( 0 + 1 ) − 3 ( 0 + 1 ) = 2 − 3 = − 1
Interesting. Thanks for sharing your idea.
Sir is this method possible for other summilar trigonometry questions.
2 ( sin 6 θ + cos 6 θ ) − 3 ( sin 4 θ + cos 4 θ ) = 2 ( sin 2 θ + cos 2 θ ) ( sin 4 θ − sin 2 θ cos 2 θ + cos 4 θ ) − 3 ( sin 4 θ + cos 4 θ ) = 2 ( 1 ) ( sin 4 θ − sin 2 θ cos 2 θ + cos 4 θ ) − 3 ( sin 4 θ + cos 4 θ ) = 2 ( sin 4 θ + cos 4 θ ) − 2 sin 2 θ cos 2 θ − 3 ( sin 4 θ + cos 4 θ ) = − ( sin 4 θ + cos 4 θ ) − 2 sin 2 θ cos 2 θ = − sin 4 θ − 2 sin 2 θ cos 2 θ − cos 4 θ = − ( sin 2 θ + cos 2 θ ) 2 = − 1 2 = − 1
Nicely done but l would mention the use of this identity in your solution a 3 + b 3 = ( a + b ) ( a 2 − a b + b 2 ) and how you replaced ( a ) by sin 2 θ and ( b ) by cos 2 θ to be extra clear. Thank you for sharing your solution.
Thank you for sharing your solution.
Problem Loading...
Note Loading...
Set Loading...
x = 2 ( sin 6 θ + cos 6 θ ) − 3 ( sin 4 θ + cos 4 θ ) = 2 ( sin 2 θ + cos 2 θ ) ( sin 4 θ + cos 4 θ − sin 2 θ cos 2 θ ) − 3 ( sin 4 θ + cos 4 θ ) = − ( sin 4 θ + cos 4 θ ) − 2 sin 2 θ cos 2 θ = − ( ( sin 2 θ + cos 2 θ ) 2 − 2 sin 2 θ cos 2 θ ) − 2 sin 2 θ cos 2 θ = − 1 Note that a 3 + b 3 = ( a + b ) ( a 2 + b 2 − a b ) Note that sin 2 x + cos 2 x = 1 Note that a 2 + b 2 = ( a + b ) 2 − 2 a b